Incidence and Distribution of Lymphoid Neoplasm of the Urinary Tract and Male Genital Organs in an Urban Area of Northern Italy in the Last Decade. Issue 23 (January 2014) - Vedovo, Francesca; Pavan, Nicola; Liguori, Giovanni; Bussani, Rossana; Siracusano, Salvatore; Trombetta, Carlo
Introduction: Lymphoid neoplasms of the urinary tract and male genital organs are relatively rare, comprising less than 5% of all primary extranodal lymphomas; only a handful of small case series and isolated case reports have been published to describe their predominant sites and subtypes. Material and Methods: We searched our institution's electronic archive of pathology reports from 2001 to 2012. We considered lymphoid neoplasms involving the kidney, bladder, testes and prostate. Patient age at diagnosis, sex, clinical history, and outcome were recorded using the relevant electronic medical records. Results: We identified 25 patients with lymphoid neoplasms of the urogenital tract. 11 cases out of 40 were primary genitourinary lymphomas. Mean age at diagnosis was 61.7 years (range 13–87 years). Among bladder lymphomas cases, a male predominance was noted. As regards the types of lymphoid neoplasms, the following subtypes were observed: diffuse large B-cell lymphoma (32%), chronic lymphocytic leukemia (24%), small lymphocytic lymphoma (20%), Malt lymphoma (8%), Burkitt lymphoma (4%), follicular lymphoma (4%); diffuse large B-cell ALK+ (4%) and lymphoblastic lymphoma (4%). Conclusions: Genitourinary tract lymphomas most commonly occurred in the kidney. B-cell non-Hodgkin's lymphomas were predominant, with diffuse large B-cell lymphoma being the most common subtype in the entire group. Although this study confirms the predominance of diffuse large B-cell lymphoma in extranodal sites, the findings also highlight the variety of lymphomas that may occur in the genitourinary tract. This diversity of subtypes affirms the importance of fully characterizing lymphomas by immunohistochemistry and other modalities, which are indispensable for accurate diagnosis.